Forming short-period substellar companions in 47 Tucanae: I. Dynamical model and brown dwarf tidal capture rates - Winter, Andrew J.; Rosotti, Giovanni Pietro; Clarke, Cathie; Giersz, Mirek (Monthly notices of the Royal Astronomical Society, 2022)
Stars in globular clusters formed and evolved in the most extreme environment: high density and low metallicity. If the formation of stars and planets is at all sensitive to environmental conditions, this should therefore be evident in globular clusters. Observations have indicated that hot Jupiters are at least an order of magnitude less prevalent in the central region of the globular cluster 47 Tucanae (Tuc) than in the field. In this work, we explore the claims in the literature for additional consequences for the low-mass stellar initial mass function. Tidal capture, the mechanism that produces X-ray binaries in globular clusters, applies also to brown dwarfs (BDs). This process produces tight stellar-BD binaries that would be detectable by transit surveys. Applying a Monte Carlo dynamical evolution model, we compute the overall BD capture rates. We find that the number of captures is lower than previous estimates. Capture efficiency increases steeply with stellar mass, which means that mass segregation reduces capture efficiency as BDs and low-mass stars occupy the same regions. The result of this effect is that the current constraints on the short-period companion fraction remain marginally consistent with initially equal numbers of BDs and stars. However, our findings suggest that expanding the sample in 47 Tuc or surveying other globular clusters for close substellar companions can yield constraints on the substellar initial mass function in these environments. We estimate the capture rates in other globular clusters and suggest that 47 Tuc remains a promising target for future transit surveys.